Characterization of the resistome and microbiome of retail meats processed from carcasses of conventionally and naturally raised cattle - Thomas, Kevin, author; Belk, Keith, advisor; Morley, Paul, committee member; Metcalf, Jessica, committee member (Colorado State University. Libraries, 2019)
Concern over human exposure to antimicrobial resistance (AMR) via consumption of meat products has raised questions about use of antimicrobial drugs in food-animal production. This concern has led to an increase in consumer demand for meat products from naturally-raised cattle, or those raised without use of antimicrobials. While previous studies have assessed AMR gene presence in cattle and throughout the beef supply chain, very little work has surveyed the resistome on retail meats available for consumer purchase. The objective of this study was to determine the extent of antimicrobial resistance and characterize the microbiome in retail ground beef products from naturally-raised (raised without antibiotics) and conventionally-raised cattle utilizing 16S rRNA and targeted shotgun metagenomic, high-throughput sequencing techniques. Differing in packaging types and lean points, samples of ground beef derived from carcasses of cattle that were conventionally-raised (n = 50) or naturally-raised cattle (n = 50) were purchased from retail outlets in six major metropolitan cities throughout the United States. Samples were shipped to Colorado State University and processed following 48 hours of refrigeration at 4°C. Thirty-gram portions of each sample were removed and subjected to DNA extraction procedures via DNeasy PowerFecal Microbial Kit. Cell lysates were composited by production system and city before being subjected to paired-end 16S rRNA gene sequencing and targeted shotgun metagenomic sequencing using an enrichment system developed in our laboratory. Microbiome analysis was performed from 16S data with QIIME2 v.2018.4 by utilizing many of the available plugins. Resistome analysis of enriched metagenomic data was performed using a modified AMRPlusPlus pipeline. Microbiome alpha diversity analysis indicated that ground beef processed from conventionally-raised animals had a greater (P < 0.05) species richness than natural ground beef products. Microbiome composition differed (P < 0.05) between samples of differing production systems based on abundance weighted UniFrac distances. Additionally, when analyzed using unweighted UniFrac distances, microbial composition differed (P < 0.05) between samples from different cities. Differences in product packaging availability between cities may have caused these differences detected in microbiome composition, as well as environmental contamination or product handling in distribution. Targeted shotgun sequencing yielded a total of 4.6 trillion reads across all 60 composite samples, with only 58 samples containing hits to AMR. Of these 58 samples, 10.1 million reads were assigned to: 520 groups, 101 mechanisms of resistance, and 22 classes of antibiotics. The three most abundant classes of resistance detected included tetracyclines (56% of assigned reads), multi-drug resistance (21% of reads), and beta-lactams (7% of reads). An analysis of similarity on samples ordinated using Euclidian distances suggested that the overall resistome differed (P < 0.05) by production system, likely driven by greater antimicrobial resistance group variation among conventional retail samples. Results from this study profiled resistance and characterized microbial composition of retail beef products from two major production practices. While the results do not discredit concern over imprudent use of antibiotics in beef production, differing management techniques in cattle production do not appear to have a direct impact on the resistome or microbiome of final retail products available to consumers.
Keywords: metagenomics; resistome; microbiome; antimicrobial resistance